A New Oceanographic Data Portal: Padjadjaran Oceanographic Data Centre (PODC) - Ibnu Faizal; Noir Primadona Purba; Darryl Anthony Valino; Madihah Jafar Sidik; Amarif Abimanyu; Tony Bratasena; Fajri Ramdhani; Ajeng Wulandari (Politeknik Kelautan dan Perikanan Dumai, 2021)
Understanding the physio-chemical oceanic and atmospheric processes is critical in monitoring climate change. Archipelagic and Small Island countries are vulnerable to the detrimental effects of climate change, and open access oceanic databases can solve data limitations leading to further development of action plans and government policies. A website was developed (www.isea-podc.org) to distribute and augment free oceanographic data based on various in-situ sampling instruments. Oceanographers review the data collected and stored in the portal. It is led by the Marine Research Laboratory (MEAL), Padjadjaran University, in partnership with Marine Science Institute (MSI), University of the Philippines. This framework supplements information that can support marine ecosystems, fisheries, and climate science studies. Furthermore, all data are accessible to not only the academe but also decision-makers in all aspects. The data sources are student research and the new instruments (RHEA and ARHEA) developed by MEAL. In the future, the portal will be integrated with other government institutional data to provide other functional features and can yield network-wide analyses. In the next phase, collaboration from ASEAN countries should be conducted to gain more impact and provide robust datasets.